(3TQM GdehLR aj GdeaQOGJs - (3Ydj Hf CHj GdMRe GdbQTj , YdGA GdOjf CHh GdMSf , GHf GdfajS,J (B687 (3g` s
(3ChdgG (B:s
(3hHYO , agPG af GdeaQOGJ ef cJGH GdehLR ai GdWH , hHGddg GdJhajb MQa GdCda (B: (3EHQjSe (B: (3eGgjJg eYQhag , MGQ ai GdChdi eaQM hNGUI GdNGe hjefY dHSg JhdO Gdbed ai dGHSg s
(3BNQgG (B:s
(3GdfbjQ KeGf bWejQGJ GdbWejQ (B: (3GKfi YTQ Odc GdLHgI (B: (3KdK bjQGW GdOGfb (B: (3fUa MHI s
(3GbJUQ Ydi TQM GdeaQOGJ abW ef GdehLRs
(3hHChd GdcJGH QSGdI ai HbGA GdUMI HMSf GdJOHjQ ai GdZPGAs
(3hOaY GdeQV HMSf GdYfGjI ai GdOhGAs
(3ceG jhLO HBNQg HYV GdahGFO GdWHjI s
(3hgh ai GdeaQOGJ hPcQ GdeQcHGJ hefGaYgG hahGFOgG s
(3bQf GdfSN (B:s
Keywords: (3GdWHs